Leishmania infantum induces high phagocytic capacity and intracellular nitric oxide production by human proinflammatory monocyte - Christiana Vargas Ribeiro; Bruna Fonte Boa Rocha; Edward Oliveira; Andrea Teixeira-Carvalho; Olindo Assis Martins-Filho; Silvane Maria Fonseca Murta; Vanessa Peruhype-Magalhães (Memorias do Instituto Oswaldo Cruz)
BACKGROUND The mechanism of resistance to SbIII in Leishmania is complex, multifactorial and involves not only biochemical mechanisms, but also other elements, such as the immune system of the host. OBJECTIVES In this study, putative changes in the immunological profile of human monocytes infected with wild-type (WT) and antimony (SbIII)-resistant Leishmania (Viannia) braziliensis and Leishmania (Leishmania) infantum lines were evaluated. METHODS Susceptibility assays WT and SbIII-resistant L. braziliensis and L. infantum were performed using lines THP-1 human monocytic lineage. Phagocytic capacity, cytokine profile, intracellular nitric oxide (NO) production and surface carbohydrate residues profile were performed in peripheral blood monocytes by flow cytometry. FINDINGS The phagocytic capacity and intracellular NO production by classical (CD14++CD16-) and proinflammatory (CD14++CD16+) monocytes were higher in the presence of L. infantum lines compared to L. braziliensis lines. The results also highlight proinflammatory monocytes as the cellular subpopulation of major relevance in a phagocytosis event and NO expression. It is important to note that L. infantum induced a proinflammatory cytokine profile characterised by higher levels of TNF-α in culture supernatant than L. braziliensis. Conversely, both Leishmania lines induce high levels of IL-6 in culture supernatant. Analysis of the expression profile of surface carbohydrates showed that L. braziliensis presents 4.3-fold higher expression of galactose(β1,4)N-acetylglucosamine than L. infantum line. Interestingly, the expression level of α-N-acetylgalactosamine residues was 2-fold lower in the SbIII-resistant L. braziliensis line than its counterpart WT line, indicating differences in surface glycoconjugates between these lines. MAIN CONCLUSIONS Our results showed that L. braziliensis and L. infantum induce different innate immune responses and a highly inflammatory profile, which is characteristic of infection by L. infantum, the species associated with visceral disease.